Analysis of Micrtoic E-Module Training Development Needs - Khairul Anshari; Kasman Rukun; Asrul Huda (Postgraduate School, Universitas Negeri Padang, 2020)
The purpose of this study is to conduct a needs analysis for the development and compilation of e- modules. The e- module was prepared to facilitate training in order to improve the competency of informatics engineering teachers in West Sumatra. The development of e- module is using the model ploom and nieveen . The development procedure consists of 3 stages , namely 1) preliminary Research 2) prototyping stage and 3) assessment phase. Research carried out in the period 6 months , to perform the analysis of the needs in some of SMK Negeri Sumatra west who have majors engineering informatics and designing e- module training . Subject of research is the teacher engineering informatics SMK Negeri that exist in West Sumatra. Analysis of the data is done by descriptive with the method of the survey . From the results of the analysis obtained that . From the results of the analysis obtained that Master requires a time that is free to carry out training so as not interfere with the process of learning to teach . Second of all teachers in need of training in the field of competence of each , such as in the field of engineering of computer networks , teachers require training on connecting cable fiber optics , build networks , administer the network and use mirotik and Cisco. Teachers also need the latest developments from the 2013 curriculum , namely materials , modules and teaching materials.